Łuk Mużakowa jako złożona struktura glacitektoniczna = The zones of glaciotectonical deformation in Muskau Arc region - Urbański, Krzysztof (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
It was proved that the main brown coal bed correlates with 2nd Lausic Seam in the Ścinawa Formation. This stratum has over 10 meter thickness. The uppermost coal layers have a little thickness and a small lateral extension. The lower coal seam belongs to the Rawicz Formation. It is not deformed.
Keywords: X jubileuszowe sympozjum glacitektoniki